Manajemen Pembelajaran Dalam Mengembangkan Kemandirian Anak Usia Dini di TK Edelweis Kelurahan Tanjung Pinang Kecamatan Jambi Timur Kota Jambi - Siti Marwah (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2020)
This study aimed to determine the Early Childhood Learning Strategy in the Development of Children's Independence in Edelweis Kindergarten, Jambi City. This research is based on the presence of children who are not yet independent in terms of the bathroom, children are still accompanied by parents in institutions until they return from school, children have not mingled with their peers. This research uses qualitative research techniques. The subjects of this study were children of group B Edelweis Kindergarten Jambi City. As for the research subjects, all stakeholders of Edelweis Kindergarten Jambi City include the principal, teachers, and students. And the informant is the Edelweis Kindergarten Teacher in Jambi City. Data collection techniques using observation, documentation, and interviews. The instrument used in the observation was in the form of research sheets, for documentation using photos to document all children's activities during activities and interviews using interview guidelines with Group B teachers to find out the conditions and problems faced. The results of this study are 1. Early childhood learning strategies in the development of children's independence in Edelweis Kindergarten Jambi City using three steps, namely a). Planning b). Implementation and c) Evaluation. 2. Constraints faced in the application of PAUD learning in the development of children's independence in Edelweis Kindergarten, Jambi City are a) Lack of supporting infrastructure in online learning activities, b), lack of parental knowledge in caring for children's growth and development, and c) Lack of parental support for children's independence so that they will not feel confident in carrying out activities. 3. The results obtained from the implementation of the Strategy, PAUD learning in the development of children's independence is the application of early childhood learning strategies in developing children's independence in Edelweis Kindergarten, Jambi City, running well in accordance with the learning objectives that have been compiled together with the parents of students, even in the middle. In the middle of a semester the learning activities turned into an online system because during the pandemic, there was Covid 19.